Strategies For Increasing Social Welfare Based On Strength In Olilit Village Tanimbar Islands Regency - Balthasar Watunglawar (Perbanas Institute, 2022)
This study aims to identify, describe, and analyze the strength factors that can be controlled and used by the village government in improving welfare; village government strategies in improving welfare related to the use of strength; factors influence the village government's strategy in improving the public prosperity. The method used to solve the research problem was descriptive qualitative research method. Informants were determined by purposive sampling technique, namely the research sample taken not depending on the number of population but adjusted to the purpose. Methods of data collection were done by interview, observation, and documentation. The data analysis technique was carried out by means of data reduction, data display, and data verification. From the results of the study, it was found that the resources of the Olilit village which were considered to be the strength of the village for improving welfare included the physical environment, tri sakti, tourism potential, culture and tradition, as well as the position of the western village in the district city. The strategy of the Olilit village government in improving the social prosperity was realized through the consistent attitude of the village government in paying attention to the operations of existing government officials and organizations, setting night study hours for students, fostering the younger generation, and providing compensation to families who were classified as poor, widows, and disabled. In addition, there are several factors that influence the implementation of the strategy, such as budget, facilities, consumerist lifestyle, political perspective of local government, and discipline.